Performance testing framework in a heterogeneous and hybrid smart grid communication network - Quang D.N.; See O.H.; Nga D.V.; Chee L.L.; Xuen C.Y.; Karuppiah S.A.L. (Maxwell Science Publications, 2023)
Heterogeneous and hybrid smart grid communication network is comprised of different communication mediums and technologies. Performance evaluation is one of the main concerns for smart grid communication system. In any smart grid communication implementation, to determine the performance factor of the network, a testing of an end-to-end process flow is required. An effective and coordinated testing procedure plays a crucial role in evaluating the performance of smart grid communications. Therefore, this study proposes a testing framework which specifies the types of communication mediums and technologies, the evaluation criteria and software tools to carry out the testing. The proposed testing scheme is used as a guideline to analyze and assess the performance of smart grid communication system. Maxwell Scientific Organization, 2013.